Studying the strength of stiffened panels in double bottom of bulk carrier under the influence of vertical pressure and horizontal axial forces using FEA - يوسف, علي; غالب أحمد; هيثم عيسى; سليمان العلي (Latakia University Journal -Engineering Sciences Series, 2024)
This research focuses on the strength analysis of stiffened panels in the double bottom of a bulk carrier ship, using Finite Element Analysis (FEA). The cross-sectional shape of the ISSC-2000 bulk carrier was considered. Using two types of Stiffeners, T and L, thirty tests for each type were conducted by FEA to predict the response of stiffened panels with including stress, buckling, and deformation, under vertical pressure and horizontal forces. It was concluded that it is necessary to use L-section strengthening elements in structure section of ships with longitudinal framing. These stiffeners offer more strength and stiffness than T-Section for the structural panels.